2016
DOI: 10.2174/1874070701610010363
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Polycyclic Aromatic Hydrocarbon (PAHs): A Perspective

Abstract: Hydrocarbon pollution is a perennial problem not only in India but throughout the globe. A plethora of microorganisms have been reported to be efficient degraders of these recalcitrant pollutants. One of the major concerns of environmental problem is the presence of hydrocarbons due to the various anthropogenic activities. PAHs are ubiquitous in naturei.e.present in soil, water and air. Presence of PAHs in environment creates problem as their presence have deleterious effect on human and animals. They also hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 95 publications
0
39
0
1
Order By: Relevance
“…It is well documented that PAHs have toxic, carcinogenic and even mutagenic effects on life organisms [1][2][3][4] . Although the human activities contributes to the PAH presence in the elevated concentrations in soils, the microorganisms such as bacteria, fungi and algae can successfully participate in the PAH biodegradation 1,5 . The effective way to decontaminate the PAHs including some physical, chemical and biological (bioremediation, phytoremediation) processes can lead to complete mineralization into CO 2 , H 2 O and biomass 6 .…”
mentioning
confidence: 99%
“…It is well documented that PAHs have toxic, carcinogenic and even mutagenic effects on life organisms [1][2][3][4] . Although the human activities contributes to the PAH presence in the elevated concentrations in soils, the microorganisms such as bacteria, fungi and algae can successfully participate in the PAH biodegradation 1,5 . The effective way to decontaminate the PAHs including some physical, chemical and biological (bioremediation, phytoremediation) processes can lead to complete mineralization into CO 2 , H 2 O and biomass 6 .…”
mentioning
confidence: 99%
“…Being the CFE site the one that contains the highest concentrations of PAHs, particularly, of fluoranthene (45.82 ng g -1 ), pyrene (39.12 ng g -1 ), and benzo (a)pyrene (26.09 ng g -1 ). It is known that LMW-PAHs are more easily biodegradable and consequently, predominant in seawater due to their partial solubility, whereas HMW-PAHs are recalcitrant and hydrophobic compounds, therefore, they can adsorb onto settling particles and reach the marine sediment bed [21,22].…”
Section: Determination Of Pahs In Surface Seawater and Marine Sedimentsmentioning
confidence: 99%
“…In general, many studies have shown that bacteria and fungi metabolite PAHs (e.g. Gupte et al, 2016;Munoz et al, 2003;Semple et al, 2003;Reid et al, 2000;Heitkamp et al, 1987 and1988). They transform PAHs to activated products such as diol-oxides (PAHs metabolites by the cytochrome P-450 or similar mechanisms).…”
Section: Correlations Between Bacteria Fungi and Pahs Concentrationsmentioning
confidence: 99%
“…It was reported that the fate of PAHs in soil is affected by various factors including biological diversity and abundance (Gupte et al, 2016;Semple et al, 2003;Reid et al, 2000;Heitkamp et al, 1988). Wood-decaying fungi can detoxify, oxidize, and transform PAH (e.g.…”
Section: Introductionmentioning
confidence: 99%